NURSES’ PERSPECTIVE TOWARDS CARING FOR JORDANIAN MEN WITH SEXUAL HEALTH PROBLEMS - Suhair Hussni Al-Ghabeesh; Muwafaq Al-Momani; Ibraheem Bashayreh; Ali Alshraifeen; Ahmad Saifan (Journal of Men's Health, 2019)
Purpose This study examined nurses’ role in their practice, nursing education and the impact of culture in Jordan on helping men suffering from sexual problems.